The Role of Agriculture in Reducing Poverty Levels in Rural Areas in North Sumatra (International Journal of Economics and Management Research, 2026)
The objective of this study is to analyze the role of the agricultural sector in reducing the level of poverty in rural areas of North Sumatra Province. The data used are secondary time series data covering the period 2015–2024, obtained from the Central Bureau of Statistics (BPS) of North Sumatra and other official sources. The variables used include the poverty rate as the dependent variable, and agricultural output growth, agricultural labor, and agricultural investment as independent variables. Data analysis was conducted using multiple linear regression with the assistance of the SPSS program. The results of the study show that agricultural output growth and agricultural investment have a negative effect on the poverty rate, meaning that an increase in these two variables is able to reduce the level of poverty in North Sumatra. Meanwhile, agricultural labor does not show a significant effect on poverty. These findings emphasize the importance of increasing productivity and investment in the agricultural sector as a strategy for poverty reduction in rural areas.